INSTRUMENTATION SYSTEMS REVOLUTIONIZING AGRICULTURE: A COMPREHENSIVE REVIEW - Mamman, E; Oni, K. C.; Ajiboye , A. T. (Research Journal of Agriculture (RJA), 2022)
Accurate measurement of parameters plays a crucial role in advancing the research and development of farm machinery. The reliability of data is imperative for the mass production of efficient agricultural machines. Instrumentation, involving computerized instruments and electronic systems, has been pivotal in achieving this accuracy. This paper delves into the realm of instrumentation in the context of agricultural machinery, addressing its significance, components, and diverse applications. The utilization of instrumentation spans various sectors, but its prominence in agriculture is indisputable. From farm surveying to processing, storage, and laboratory experiments, instrumentation finds multifaceted applications. Notable advancements have been witnessed in electronic instrumentation systems, with components such as load cells, strain gauges, sensors, and transducers gaining prominence. To exemplify the practical application of instrumentation, the study highlights several instances. Owende and Ward's (1997) low-cost data acquisition system, the towed ring, is an embodiment of this technology. John et al. (2007) used pressure transducers to evaluate soil post-load responses, and cone penetrometers with load cells have been employed to assess soil strength and density. Mardani et al. (2010) and Ale et al. (2013) developed instrumentation systems for draught and compaction measurement. In the context of precision seed planting, monitoring tools have emerged for quantifying planting quality and quantity. Utilizing technologies like photoelectric and piezoelectric effects, infra-red sensors, and single-chip microcomputers, these systems enhance the accuracy of planting operations. Techniques like electromagnetic induction, magnetic resistance effects, and the hall effect have also proven valuable in quality and quantity measurement, even in harsh environments. The study's focal point is the automatic measurement of draught and counting of planted stakes in cassava planters. Achieving these goals necessitates sophisticated instrumentation systems. This paper presents a comprehensive exploration of the theoretical and practical aspects of agricultural instrumentation, shedding light on its pervasive influence across diverse stages of farming processes. Through the integration of electronic components and advanced sensing technologies, instrumentation continues to play a pivotal role in reshaping agricultural practices for enhanced productivity and efficiency.